Charakterystyka dochodów własnych budżetów gmin w Polsce w ujęciu przestrzennym w latach 2004–2011 w procesie instytucjonalizacji stosunków międzynarodowych - Jarosiński, Krzysztof (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
The paper concentrates on budgetary income of Polish gminas. The text is part of larger study on Polish local government budgetary policies. In the period beginning in 2004 and ending in 2011 no significant shrinking of disparities between regions have been observed and in some cases they have even increased. At the same time income of local government in Poland increased. Main reasons why the disparities persists are twofold: 1. different dynamics of development and 2. different economic foundations. Although the disparities in income between gimans increased, incomes of all gimnas increased at the same time. This allowed for implementation of new local policies which led to new impulses for growth, financed either by gminas or by the EU